Immunohistochemical Analysis of Scarring Trachoma Indicates Infiltration by Natural Killer and Undefined CD45 Negative Cells - Hu, Victor H.; Luthert, Philip J.; Derrick, Tamsyn; Pullin, James; Weiss, Helen A.; Massae, Patrick; Mtuy, Tara; Makupa, William; Essex, David; Mabey, David C. W.; Bailey, Robin L.; Holland, Martin J.; et al. (PLoS neglected tropical diseases, 2016)
The phenotype and function of immune cells infiltrating the conjunctiva in scarring trachoma have yet to be fully characterized. We assessed tissue morphology and immunophenotype of cellular infiltrates found in trachomatous scarring compared to control participants. Clinical assessments and conjunctival biopsy samples were obtained from 34 individuals with trachomatous scarring undergoing trichiasis surgery and 33 control subjects undergoing cataract or retinal detachment surgery. Biopsy samples were fixed in buffered formalin and embedded in paraffin wax. Hematoxylin and eosin (H&E) staining was performed for assessment of the inflammatory cell infiltrate. Immunohistochemical staining of single markers on individual sections was performed to identify cells expressing CD3 (T-cells), CD4 (helper T-cells), CD8 (suppressor/cytotoxic T-cells and Natural Killer, NK, cells), NCR1 (NK cells), CD20 (B-cells), CD45 (nucleated hematopoietic cells), CD56 (NK and T-cells), CD68 (macrophages/monocytes) and CD83 (mature dendritic cells). The degree of scarring was assessed histologically using cross-polarized light to visualize collagen fibres. Scarring, regardless of clinical inflammation, was associated with increased inflammatory cell infiltrates on H&E and CD45 staining. Scarring was also associated with increased CD8+ and CD56+ cells, but not CD3+ cells, suggestive of a NK cell infiltrate. This was supported by the presence of NCR1+ cells. There was some increase in CD20+ cells, but no evidence for increased CD4+, CD68+ or CD83+ cells. Numerous CD45 negative cells were also seen in the population of infiltrating inflammatory cells in scarred conjunctiva. Disorganization of the normal collagen architecture was strongly associated with clinical scarring. These data point to the infiltration of immune cells with a phenotype suggestive of NK cells in conjunctival trachomatous scarring. A large proportion of CD45 negative inflammatory cells were also present. Future work should seek to understand the stimuli leading to the recruitment of these cells and their role in progressive scarring.